Alcohol-related harm in emergency departments: A prospective, multi-centre study - Egerton-Warburton, Diana; Gosbell, A.; Moore, K.; Wadsworth, A.; Richardson, D.; Fatovich, D. (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 Society for the Study of Addiction. Background: Emergency department (ED) alcohol-related presentation data are not collected routinely. It is likely that previous research has underestimated the numbers of patients presenting with alcohol-related conditions. Design: Multi-centre, prospective study. Patients were screened prospectively for alcohol-related presentations during a 7-day period in December 2014. Part 1 involved screening to determine alcohol-positive ED presentations and data collection of patient demographic and clinical information. Part 2 involved a consent-based survey conducted with patients aged = 14 years to perform Alcohol Use Disorders Identification Test (AUDIT) scores. Setting: Eight EDs in Australia and New Zealand, representing differing hospital role delineations. Participants: A total of 8652 patients aged = 14 years attended and 8435 (97.5%) were screened. Measurements: The main outcome measure was the proportion of patients who had an alcohol-related presentation termed 'alcohol-positive', using pre-defined criteria. It included injuries, intoxication, medical conditions and injuries caused by an alcohol-affected third party. Secondary outcomes included demographic and clinical information, the type of alcohol-related presentations and AUDIT scores. Findings: A total of 801 [9.5%; 95% confidence interval (CI) = 8.9-10.1%] presentations were identified as alcohol-positive, ranging between 4.9 and 15.2% throughout sites. Compared with alcohol-negative patients, alcohol-positive patients were more likely to be male [odds ratio (OR) = 1.90, 95% CI = 1.63-2.21] , younger (median age 37 versus 46 years, P < 0.0001), arrive by ambulance (OR = 1.94, 95% CI = 1.68-2.25) or police/correctional vehicle (OR = 4.56, 95% CI = 3.05-6.81) and require immediate treatment (OR = 3.20, 95% CI = 2.03-05.06). The median AUDIT score was 16 (interquartile range = 10-24). Conclusions: Almost one in 10 presentations to emergency departments in Australia and New Zealand are alcohol related.